Attitude of Hearing Impaired Students towards Inclusive Education in Pakistan - Abid Masood Khan، Abdul Sami، Afsheen Salahuddin (JIE, 2024)
In many societies the idea of education for special needs children has been changed since last few decades. However, the hearing impaired students are not enjoying their educational right in inclusive class like that of their hearing counterparts. Hence, this study was intended to analyze the attitude and perception of hearing impaired students towards inclusive education in Pakistan. An exploratory research design was used in the present study and as this was a descriptive research so survey method was used to collect the data for this study.